Impurity removal with highly selective and efficient methods and the recycling of transition metals from spent lithium-ion batteries. Issue 38 (16th July 2019) - Peng, Fangwei; Mu, Deying; Li, Ruhong; Liu, Yuanlong; Ji, Yuanpeng; Dai, Changsong; Ding, Fei
Abstract : A strategy for metal purification and recovery from spent lithium-ion batteries is demonstrated by taking advantage of precipitation, electrodeposition and solvent extraction. Abstract : The use of lithium-ion batteries (LIBs) is skyrocketing since they are widely applied in portable consumer devices and electric vehicles. However, at the end of their lifetime, large amount of spent LIBs will result in a negative environmental impact and aggravate the problem of resource shortage without proper disposal. Therefore, recycling is an effective solution, which will be enforced in the near future. Herein, the purification, recovery and reuse of transition metals from spent LIBs were thoroughly studied. First, the target impurities in a solution were effectively removed individually. Iron(iii ) and aluminum(iii ) impurities were removed by adjusting the pH value, whereas copper(ii ) was purified using highly selective electrodeposition technology and solvent extraction. Second, Ni0.41 Co0.21 Mn0.38 (OH)2 was co-precipitated by adjusting the pH value of the purified metal solution, containing nickel(ii ), cobalt(ii ) and manganese(ii ) ions to 11 with NaOH and a proper amount of NH3 ·H2 O. The comprehensive loss in nickel(ii ), cobalt(ii ) and manganese(ii ) was only 0.37% in the purification and co-precipitation procedures. Finally, LiNi0.41 Co0.21 Mn0.38 O2 (marked as LNCM-R) synthesized with the recycled materials was tested and compared with LiNi0.41 Co0.21 Mn0.38 O2 (marked as LNCM-N) synthesized with new materials as the control group. The XRD, SEM and TEM results indicate that both samples have the same structure and morphology. Furthermore, the charge–discharge tests, initial d Q /d V curves, EIS and GITT results indicate a similar electrochemical performance of the LNCM-R and LNCM-N samples. The purification and recycling strategies in our research have high efficiency and comparatively low cost, which provide great guidance for the industrial recycling of spent Li-ion batteries.